Contributions of Mexican mathematicians abroad in pure and applied mathematics : second meeting, Matemáticos Mexicanos en el Mundo, December 15-19, 2014, Centro de Investigación en Matemáticas, Guanajuato, Mexico - Galaz-García, Fernando; Pardo, J. C.; Solórzano, Pedro; Reunión de Matemáticos Mexicanos en el Mundo (Aportaciones matematicas / Sociedad Matematica Mexicana, 2018)
This volume contains the proceedings of the Second Workshop of Mexican Mathematicians Abroad (II Reunion de Matematicos Mexicanos en el Mundo), held from December 15-19, 2014, at Centro de Investigacion en Matematicas (CIMAT) in Guanajuato, Mexico.This meeting was the second in a series of ongoing biannual meetings aimed at showcasing the research of Mexican mathematicians based outside of Mexico.The book features articles drawn from eight broad research areas: algebra, analysis, applied mathematics, combinatorics, dynamical systems, geometry, probability theory, and topology. Their topics range from novel applications of non-commutative probability to graph theory, to interactions between dynamical systems and geophysical flows.Several articles survey the fields and problems on which the authors work, highlighting research lines currently underrepresented in Mexico. The research-oriented articles provide either alternative approaches to well-known problems or new advances in active research fields. The wide selection of topics makes the book accessible to advanced graduate students and researchers in mathematics from different fields.This book is published in cooperation with Sociedad Matematica Mexicana.